Generation of induced pluripotent stem cell lines from five individuals from two families carrying a pathogenic Dutch MYBPC3 founder variant with variable degrees of hypertrophic cardiomyopathy - van den Dolder, Floor W.; Warnaar, Vincent A.J.; Onderwater, Yeszamin L.; Baas, Annette F.; Kuster, Diederik W.D.; van der Velden, Jolanda (Elsevier, 2025)
Hypertrophic cardiomyopathy (HCM) is often caused by pathogenic or likely pathogenic variants, of which 30–50 % involve a variant in the gene encoding cardiac myosin-binding protein-C (MYBPC3). We generated human induced pluripotent stem cell lines from five individuals from two families carrying a pathogenic Dutch MYBPC3 founder variant: c.2373insG (n = 2) and c.2827C > T (n = 3), with highly variable disease expression. Peripheral blood mononuclear cells were reprogrammed using episomal plasmids. All cell lines express pluripotent markers, exhibit a normal karyotype, and could differentiate into derivatives of each germ layers in vitro. These cell lines can serve as disease model to investigate HCM pathogenesis.
Keywords: Developmental Biology; Cell Biology